112 A CASE OF INCESSANT SLOW-FAST AVNRT TREATED WITH HIS BUNDLE PACING. (15th December 2022) - Rizzello, Davide; Francesca Notarangelo, Maria; Crocamo, Antonio; Gonzi, Gianluca; Mattioli, Maria; Paoli, Giorgia
Abstract: Introduction: Slow-fast AVNRT can rarely present as incessant SVT, particularly in patients with increased HV interval. We describe a case of incessant typical AVNRT, treated without transcatheter ablation. Case Presentation: An 83-year-old man, with history of PAF, was admitted to our ICU complaining of dyspnea, dizziness and amaurosis. His ECG at presentation depicted sinus bradycardia, first degree AVB (PQ=400 ms) and RBBB (Fig 1A). After betablocker wash-out period, we decided to perform CSP using HBP to ensure AV synchrony and restore physiological pacing. During wash-out period, an incessant regular wide complex tachycardia with RBBB morphology and ventricular rate of 110 bpm occurred: the tracing showed a P wave immediately after the QRS, with RP < PR (Fig 1B). The tachycardia was incessant also in the EP lab. By means of 2 pacing leads (RV lead in the apical septum and RA lead in right appendage) and one diagnostic decapolar catheter (Inquiry, 2-2-2 Abbott) in His region, all connected to the polygraph, we performed an EPS. HV interval in sinus rhythm was 60 ms, AH 340 ms. The electrograms during tachycardia showed HVA sequence and 1:1 VA association, VA< 70 ms, cycle length 520 ms. Pacing from RV lead, we performed the ventricular overdrive pacing maneuver obtaining a VAV response; PPI-TCL was 280 ms and SA-VA difference was 205 ms (Fig 2A). We also noted a VA linking response to atrial overdrive pacing, and AHA response at the end of maneuver excluding JT (Fig 2B). In addition, pacing by the His catheter during tachycardia, we interrupted the arrythmia: the V signal after the last paced beat was not followed by retro-conducted A signal (Fig 2C). Finally, by administrating adenosine 12 mg the tachycardia interrupted with A as last signal recorded (Fig 2D). All these findings were consistent with an incessant typical AVNRT. We chose to treat AVRNT with sequential atrial-His pacing, placing a third lead in His region and programming the device in DDD 70-120, with selective His bundle capture, not correcting the RBBB (Fig 1C, D). Discussion: In patients with poor anterograde AV nodal conduction, also slow-fast AVNRT can present as incessant tachycardia. In fact, a shorter sinus cycle length or atrial extrasystole could initiate sufficient delay in anterograde conduction to allow for recovery in conduction in the retrograde direction led to a persistent tachycardia. This case highlights the value of performing EPS diagnostic maneuvers also during PM implantations in order to personalize therapy and programming.